Literatur review : Konsumsi teh hijau (Camellia sinensis) terhadap penurunan tekanan darah pada penderita hipertensi - Azizah, Mulia Fadhilatul; Rahmiwati, Anita; Novrikasari, Novrikasari (Poltekkes Kemenkes Aceh, 2024)
Background: A patient is diagnosed with hypertension if their diastolic blood pressure regularly rises to 90 mmHg or higher on multiple examinations, and their systolic blood pressure regularly rises to 140 mmHg or higher. Tea is a functional food that has quite high antioxidant, anti-inflammatory, antimicrobial and anti-hypertensive content.Objectives: It is necessary to find out there is a connection between drinking green tea and lowering blood pressure in people with hypertension.Methods: This research uses a Systematic Literature Review with the PRISMA method. Protocol and SLR evaluation was carried out using the PRISMA method to select the research articles used. Articles obtained from Science Direct, PubMed, and Google Scholar. Keywords use English and Indonesian. Search terms in Indonesian included “green tea and blood pressure” OR “camellia sinensis and blood pressure” OR “green tea and hypertension” OR “camellia sinensis and hypertension”. Meanwhile, search terms in English include